Analysing Ukraine’s bilateral trade flows in goods with the European Union: a gravity model approach - Florindo, Emmanuel Fernandes (2019)
We study the main determinants of international trade flows in goods between Ukraine and the EU-28 member states in the period 1995-2017. We estimate the augmented gravity model of international trade with robust Ordinary Least Squares (OLS) and Poisson (PPML), and PPML with fixed effects too estimate trade elasticities for total trade, exports and imports functions. The regression results are used to recommend trade policy makers on the implementation of the EU Association Free-Trade Agreement with Ukraine. The main findings reveal that, the income of Ukraine, the income of the EU-28 trading partners, distance but also income differences between Ukraine and its trading partners (Linder hypothesis), and the real exchange rate are important determinants of international trade. These results are robust to different trade specification functions of the augmented gravity model of international trade.